2020
DOI: 10.24136/eq.2020.016
|View full text |Cite
|
Sign up to set email alerts
|

Intention to move and residential satisfaction: evidence from Poland

Abstract: Research background: Residential mobility affects the spatial structure of cities and urban development. Longer-distance migration has many additional implications: it affects the demographic situation of a sending area as well as its growth prospects. The literature on interregional and especially international migration regards residential satisfaction as being of at least secondary importance. More attention to this concept is given in research on intra-urban migration and suburbanisation. In a seminal pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…This assumption, although requiring further evidence, might have important implications for regional and urban policies and highlights the value of regional universities even if they do not excel on the national scale. However, the low out-migration rate of graduates compared to other countries could also be related to a relatively low overall internal mobility in Poland (Maleszyk, Kędra 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This assumption, although requiring further evidence, might have important implications for regional and urban policies and highlights the value of regional universities even if they do not excel on the national scale. However, the low out-migration rate of graduates compared to other countries could also be related to a relatively low overall internal mobility in Poland (Maleszyk, Kędra 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Residential satisfaction is defined as “the feeling of contentment when one possesses or achieves what one needs or desires at home and in its neighbourhood” (Maleszyk & Kędra, 2020, p. 342; see also Mohit & Azim, 2012; Speare, 1974). It encompasses both physical and social characteristics of a place (Aksel & Imamoğlu, 2020; Mesch & Manor, 1998), including both community atmosphere and people's involvement and interactions with community members.…”
Section: Residential Satisfaction Family and Intentions To Staymentioning
confidence: 99%
“…It encompasses both physical and social characteristics of a place (Aksel & Imamoğlu, 2020; Mesch & Manor, 1998), including both community atmosphere and people's involvement and interactions with community members. Following Speare (1974), research has found residential satisfaction to predict intentions to stay (e.g., Fang, 2006; Maleszyk & Kędra, 2020). This relationship is not always straightforward and may be moderated or counteracted by factors such as age, life course changes, work, income, and family considerations (Ginsberg & Churchman, 1984; Landale & Guest, 1985).…”
Section: Residential Satisfaction Family and Intentions To Staymentioning
confidence: 99%
“…The Polish migration policy, including the rules for foreigners' influx, has for many years been in the focus of interest of researchers dealing with the spatial movement of populations (Głąbicka, Okólski, and Stola, 1998;Iglicka et al, 2005;Kaczmarczyk and Okólski, 2008;Duszczyk, 2012;Łodziński and Szonert, 2016). An essential contribution to the resources of knowledge about the migration situation in Poland is also studied addressing the issue of the most current phenomena related to, among other things, Brexit, interregional migration, or the new directions of economic migration (Kisiel, Lizińska, and Rosochacka, 2019;Organiściak-Krzykowska, Piotrowski, and Ciulkin, 2020;Marks-Bielska, 2019;Kowalewska, Nieżurawska-Zając and Duarte, 2019;Maleszyk and Kędra, 2020).…”
Section: Introductionmentioning
confidence: 99%